Chromatin remodeling in replication‐uncoupled maintenance DNA methylation and chromosome stability: Insights from ICF syndrome studies. (7th May 2021) - Unoki, Motoko
Abstract: Immunodeficiency, centromeric instability, and facial anomalies (ICF) syndrome is characterized by frequent appearance of multiradial chromosomes, which are distinctive chromosome fusions that occur at hypomethylated pericentromeric regions comprising repetitive sequences, in activated lymphocytes. The syndrome is caused by mutations in DNMT3B, ZBTB24, CDCA7, or HELLS . De novo DNA methylation is likely defective in patients with ICF syndrome harboring mutations in DNMT3B, whereas accumulating evidence suggests that replication‐uncoupled maintenance DNA methylation of late‐replicating regions is impaired in patients with ICF syndrome harboring mutations in ZBTB24, CDCA7, or HELLS . ZBTB24 is a transcriptional activator of CDCA7, and CDCA7 and HELLS compose a chromatin remodeling complex and are involved in the maintenance DNA methylation through an interaction with UHRF1 in a feed‐forward manner. Furthermore, our recent studies possibly provided the missing link between DNA hypomethylation and the formation of the abnormal chromosomes; it could occur via aberrant transcription from the hypomethylated regions, followed by pathological R‐loop formation. The homologous‐recombination dominant condition caused by a defect in nonhomologous end joining observed in several types of ICF syndrome could facilitate the formation of multiradial chromosomes. Here, the latest knowledge regarding maintenance DNA methylation and chromosome stability provided by those studies is reviewed. Abstract : DNA methylation is maintained in either replication‐coupled or ‐uncoupled manners. The CDCA7/HELLS chromatin remodeling complex, which is mutated in ICF syndrome, contributes to centromeric/pericentromeric stability plausibly by facilitating the replication‐uncoupled process.